New Azo Derivative of β-Diketones and Its Cu(II), Co(II) Complexes: Synthesis, Theoretical Study and Biological Activity - Tahirli, Shahla; Sadeghian, Nastaran; Aliyeva, Farqana; Sujayev, Afsun; Gunay, Sevilay; Erden, Yavuz; Shikhaliyev, Namig; Erden, Yavuz; Sadeghian, Nastaran (Wiley-V C H Verlag Gmbh, 2024)
The paper is focused on biological activity and theoretical study of the structure and properties of a new azo derivative of beta-diketones and its complexes with some metals. The aim of our work was to study the structure and properties of the newly synthesized compound as well as to theoretically determine the possibility of complex formation with the Cu(II) or Co(II) ions. A compound with the same substituents R1=R2=CH3 was chosen for the study. A synthesized azo compound based on 4-amino antipyrine and its complexes with Cu(II), Co(II) in solution and solid phase is reported. The structures of these compounds have been testified by X-ray, IR and NMR spectroscopy. The combined experimental and theoretical approach was used. To study the structure and properties of the synthesized compound, as well as its possible complex formation with the Cu(II), quantum-chemical calculations were carried out the 6-31G basis set and the electron density functional theory (DFT) method. These 3-(1-phenyl-2,3-dimethyl-pyrazolone-5) azopentadione-2,4 (PDPA) with Cu(II) and Co(II) complexes had effective inhibition against butyrylcholinesterase and acetylcholinesterase. IC50 values were found as 19.03, 3.64 mu M for AChE and 28.47, 8.01 mu M for BChE, respectively. Cholinesterase inhibitors work to slow down the acetylcholine's deterioration. image
Keywords: Cu(Ii); Co(Ii) Complex; X-Ray; Dft Analysis; Anticancer; Bioactivity